Revisiting Laportea: Quercetin as A Key Bioactive for Natural Diabetes Therapy - Muhammad Nurul Fadel; Arifah Sri Wahyuni; Rima Munawaroh (GLOBAL HEALTH SCIENCE GROUP, 2026)
Insulin injections and oral hypoglycemic drugs are the main therapies available for the treatment of diabetes. However, side effects and dependence make many sufferers not continue treatment. The development of plant-based antidiabetic alternatives continues, one of which is the genus Laportea, which contains flavonoids and derivative compounds, such as quercetin, that are able to control blood sugar. The purpose of this literature review is to provide evidence-based information on the potential content of quercetin in Laportea. This literature review was created by searching databases such as: Pubmed, Elsevier, Science Direct, and Google Scholar. Searches on Elsevier and google Scholar were conducted using the following keywords: